Does Coronal Suturectomies and Occipital Barrel Staves Make a Difference in Early Reconstruction for Sagittal Craniosynostosis?. Issue 7 (October 2021) - Unander-Scharin, Jesper; Heliövaara, Arja; Enblad, Per; Leikola, Junnu; Nowinski, Daniel
Abstract : Background: Various surgical methods are used for early treatment of nonsyndromic sagittal craniosynostosis. The craniofacial centers in Uppsala and Helsinki fundamentally both use the H-Craniectomy: Renier's technique. However, the Helsinki group systematically adds coronal suturectomies to prevent secondary coronal synostosis and posterior barrel staves to address posterior bulleting. The effects of these additions in early treatment of sagittal craniosynostosis are currently unknown. Methods: Thirty-six patients from Uppsala and 27 patients from Helsinki were included in the study. Clinical data and computed tomography scans were retrieved for all patients. Results: The Helsinki patients had a smaller preoperative Cranial index (CI) (65 vs 72) and a smaller preoperative width (10.1 vs 11.2). There was no difference in postoperative CI, corresponding to a difference in change in CI. Regression analysis indicated that the larger change in CI in the Helsinki group was mainly due to a lower preoperative CI allowing for a larger normalization. The Helsinki patients had less growth in length (1.5 vs 2.1 cm) and more growth in width (2.3 vs 1.9 cm). There were no differences in head circumference or surgical complications. Secondary coronal synostosis was present in 43% of the Uppsala group at 3 years of age, while calvarial defects located at sites of previous coronal suturectomies and posterior barrel staving were seen in the Helsinki group 1 year postoperatively. Conclusions: Lower preoperative CI appears to be the main factor in determining the amount of normalization in CI. Prophylactic coronal suturectomies do not seem to benefit preservation of coronal growth function since the modification correlates to less sagittal growth and more growth in width. Abstract : Supplemental Digital Content is available in the text